MODELING DISPERSION OF LEACHATE BY USING MINITAB SOFTWARE AND SPATIAL ANALYSIS OF GROUNDWATER QUALITY AROUND LANDFILL - Fardiansyah Fardiansyah; Yasri Yasri; Tangahu Tangahu; Bieby Voijant (Proceedings of the 1st International Conference on Social Science (ICSS), 2022)
Based on previous research, already calculation of groundwater pollution index in Jabon Landfill, where from the calculation results of 12 well points in the area around TPA, the pollution index is included moderate pollution index. Based on that information, it is necessary for modeling perception of leachate penetration, to find out how far the radius of groundwater has been polluted by landfill leachate. This modeling is use minitab 17 software. Minitab was chosen because minitab is one of the most applicable software for engineering, and minitab provides a simple to understand alternative in performing statistical analysis. This study is use a non linear regression procedure to obtain a curve fitting. In this curve fitting analysis produces a formulation that can be applied to determine radius of dispersion of leachate penetration into groundwater, and based on this formulation can calculate the groundwater pollution index in the area around the landfill. Based on the calculation of the pollution index, radius 3691 meters from the landfill is classified as a moderate pollution index with a pollution index value of 9.0495. This research also evaluates the groundwater quality by mapping approach using a geographic information system. Geographic information system is an information system designed to work with spatially referenced data or geographic coordinates. So that it can provide more information about the quality of groundwater in the area.